Address Terms among the Russian Ethnic Minority in Lithuania in Offline and Online Communication: an Emerging New Identity - Korostenskiene, Julija; Belovodskaja, Anastasija (Studies of Transition States and Societies, 2020)
The study examines address terms (ATs) used by the Russian ethnic minority of Lithuania (RuL) focusing primarily on the vocative use of anthroponyms and on the zero vocative, including in combination with T/V forms of address. Our aim is to explore how ethnic and social characteristics of offline and online communities can influence address strategies in a multicultural environment and assess possible communicative risks. The article draws on the findings from two studies. We first present data from a survey conducted among RuL speakers examining their prevalent ATs, used alongside T/V forms, in offline communication. We then analyse ATs in the publications and comments sections in popular Facebook social network groups used by the RuL community. The study examines the speech behaviour of the RuL community in light of the geopolitical and sociolinguistic situation and seeks to determine factors influencing the choice of a particular form of address. The findings suggest that the RuL speakers present an emerging new identity of Russian speakers and have implications for future research on the enregisterment practices of ATs among Russian speakers of the post-Soviet space.